2020
DOI: 10.15585/mmwr.mm6943a1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplement Use in Children and Adolescents Aged ≤19 Years — United States, 2017–2018

Abstract: Dietary supplement use is common among children and adolescents. During 2013-2014, approximately one third of children and adolescents (persons aged ≤19 years) in the United States were reported to use a dietary supplement in the past 30 days, and use varied by demographic characteristics (1,2). Dietary supplements can contribute substantially to overall nutrient intake, having the potential to both mitigate nutrient shortfalls as well as to lead to nutrient intake above recommended upper limits (3). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 7 publications
4
27
0
Order By: Relevance
“…An analysis of NHANES data from 1999–2012 among adults, showed the 30-day use of vitamin C supplements, including from multi-vitamins decreased significantly from 42% to 36% [ 57 ], but more recent data are not available. Published data on trends among children/adolescents are not available but data from 2017–2018 NHANES show only 3.0% were taking a single ingredient vitamin C supplement and 23.8% were taking some type of multivitamin/multimineral supplement, which usually contain vitamin C [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of NHANES data from 1999–2012 among adults, showed the 30-day use of vitamin C supplements, including from multi-vitamins decreased significantly from 42% to 36% [ 57 ], but more recent data are not available. Published data on trends among children/adolescents are not available but data from 2017–2018 NHANES show only 3.0% were taking a single ingredient vitamin C supplement and 23.8% were taking some type of multivitamin/multimineral supplement, which usually contain vitamin C [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior reports in children, the most frequently used supplements were multivitamin/mineral products. 5,31 Female youth runners were more likely to use dietary supplements than male runners. Several prior investigations also report higher use of supplements in female youth athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Our reported prevalence (26.1%) of supplement use is lower than estimates previously reported in youth athletes and the general population. 5,[29][30][31][32] This might be related to many of our respondents being younger than athlete respondents from prior investigations, as increasing age has been associated with higher supplement use in athletes. 26,27 We identified that each year older at time of survey completion was associated with a 20% higher likelihood of supplement use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NHANES 2017-2018 survey also evaluated MVM use among children, with 23.8% of children using a MVM product in the past 30 days. 3 This included 11% of those <2 years old, 34.6% between 2 and 5 years old, 29.5% between 6 and 11 years old, and 17.3% between 12 and 19 years old. 3…”
Section: Introductionmentioning
confidence: 99%